PELATIHAN EVAKUASI BENCANA GEMPA BUMI DAN TSUNAMI DI DAYAH IHYAAUSSUNNAH KOTA LHOKSEUMAWE - Wheny Utariningsih; Khairunnisa Z; Fera Novalia (LPPM dan PM Universitas Samudra, 2021)
ABSTRACT Lhoksumawe is a city in Banda Aceh Province which is at high risk of a tsunami disaster. Based on the Kajian Risiko Bencana Aceh 2016-2020, in Lhoseumawe City there were 6,032 people who were exposed to the tsunami disaster. There are 125 schools that are threatened by the danger of the earthquake and tsunami, including schools that implement boarding schools. Twenty-four hours of the life of students in schools that apply boarding school are in school. So that schools must prepare their students to face the dangers that threaten them, namely by increasing the knowledge of students. One school that implements a boarding school in Lhokseumawe City is Dayah Modern Ihyaaussunnah. Dayah Modern Ihyaaussunnah is only 1 km from the beach. The purpose of this community service activity is to produce changes in participants' perspectives on disasters, increase understanding, awareness, preparedness, and ability to face and evacuate when an earthquake and tsunami disaster occurs in schools. As for the output target, the knowledge of Dayah Modern Ihyaaussunnah students in dealing with the earthquake and tsunami disaster and the realization of the Dayah Modern Ihyaaussunnah preparedness in the face of earthquake and tsunami disasters. The methods used in this education are lectures and simulations / demonstrations with games. Based on the data obtained, this training was able to increase students' knowledge by up to 44%